Concurrently enhanced dielectric properties and thermal conductivity in PVDF composites with core-shell structured β-SiCw@SiO2 whiskers. (October 2020) - Zhou, Wenying; Li, Xu; Zhang, Fan; Zhang, Caihua; Li, Zhen; Chen, Fuxin; Cai, Huiwu; Liu, Xiangrong; Chen, Qingguo; Dang, Zhi-Min
Abstract: To restrain dielectric loss while still simultaneously harvesting high dielectric constant ( k ) and thermal conductivity (TC) in polymer composites, β -silicon carbide whiskers ( β -SiCw ) were encapsulated by a thin insulating oxidation layer (SiO2 ) via calcination under air, and the obtained core-shell β -SiCw @SiO2 was incorporated into poly(vinylidene fluoride) (PVDF) composites. The k can be significantly enhanced in the PVDF composites with β -SiCw @SiO2, and the loss and conductivity are remarkably suppressed to very low levels even at high filler loadings. The improved dielectric performance can be attributed to the insulating SiO2 shell preventing the β -SiCw from direct contact and meanwhile impeding the long-range electron migration. Additionally, the β -SiCw @SiO2 /PVDF exhibit higher TC and mechanical properties than the β -SiCw /PVDF due to the suppressed thermal interfacial resistance and enhanced interfacial compatibility between the fillers and the matrix. Composites with high TC and k but low loss are promising materials for potential applications in microelectronic industry.